E-Human Resource Management Thought And Words - In The Human, Organization, Communication, and Technology - Ima Dwitawati (Elkawnie: Journal of Islamic Science and Technology, 2017)
Human resource factor is a mainly asset in the enterprise, because it has a unique characteristic and will not easy to imitated by the competitor. To make a well management of human resource process and its development in the enterprise is important. Together with the coming of information era, then the utilization of information technology to manage and develop the human resource is really necessary. Its means the human resources which managed traditionally would be change by manage it electronically. In the other word, the term of human resource management (HRM) changed by electronic human resource management (e-HRM). Certainly, to develop and manage e-HRM continuously is not easy without the consideration of such factors that exist within it as: human, organization, communication, and technology factors. Therefore, in this article explained such factor that will encourage these four factors in e-HRM practice, with the result is the e-HRM well management, and finally will increase the human resource development in the enterprise. After the consideration of human, organization, communication and technology factor, then continue by analyzed ten of social theory and used it to encourage the e-HRM development perfectly, where the utilization of each social theory is adjusted with appropriate factor only. The social theories that used in this article are: 1) Attribution theory, 2) Act* theory, 3) Argumentation theory, 4) Contagion theory, 5) Cognitive dissonance theory, 6) Agenda setting theory, 7) Absorptive capacity theory, 8) Actor network theory, 9) Adaptive structuration theory, and 10) Administrative behavior theory. Furthermore, the last part of this article is an explanation of human, organization, ommunication, and technology factor, and how to make each factor will give an effective function in e-HRM practice by using the social theory style in order the development of e-HRM more effective, efficient, and increase continuously.